A dissociation between syntactic and lexical processing in Parkinson's disease. (August 2019) - Johari, Karim; Walenski, Matthew; Reifegerste, Jana; Ashrafi, Farzad; Behroozmand, Roozbeh; Daemi, Mostafa; Ullman, Michael T.
Abstract: Parkinson's disease (PD), which involves the degeneration of dopaminergic neurons in the basal ganglia, has long been associated with motor deficits. Increasing evidence suggests that language can also be impaired, including aspects of syntactic and lexical processing. However, the exact pattern of these impairments remains somewhat unclear, for several reasons. Few studies have examined and compared syntactic and lexical processing within subjects, so their relative deficits remain to be elucidated. Studies have focused on earlier stages of PD, so syntactic and lexical processing in later stages are less well understood. Research has largely probed English and a handful of other European languages, and it is unclear whether findings generalize more broadly. Finally, few studies have examined links between syntactic/lexical impairments and their neurocognitive substrates, such as measures of basal ganglia degeneration or dopaminergic processes. We addressed these gaps by investigating multiple aspects of Farsi syntactic and lexical processing in 40 Farsi native-speaking moderate-to-severe non-demented PD patients, and 40 healthy controls. Analyses revealed equivalent impairments of syntactic comprehension and syntactic judgment, across different syntactic structures. Lexical processing was impaired only for motor function-related objects (e.g., naming 'hammer', but not 'mountain'), in line with findings of PD deficits at naming action verbs as compared to objects, without the verb/noun confound. In direct comparisons between lexical and syntactic tasks, patients were better at naming words like 'mountain' (but not words like 'hammer') than at syntactic comprehension and syntactic judgment. Performance at syntactic comprehension correlated with the last levodopa equivalent dose. No other correlations were found between syntactic/lexical processing measures and either levodopa equivalent dose or hypokinesia, which reflects degeneration of basal ganglia motor-related circuits. All critical significant main effects, interactions, and correlations yielded large effect sizes. The findings elucidate the nature of syntactic and lexical processing impairments in PD. Highlights: We probed syntactic and lexical processing in Farsi-speaking Parkinson's patients. Syntax showed clear deficits: in judgment and comprehension, across structures. Lexical processing was unimpaired, except for motor-related words (e.g., hammer). Syntactic comprehension was modulated by patients' last levodopa equivalent dose. The study elucidates language in Parkinson's, moreover in an understudied language.